2017
DOI: 10.1177/1357633x17704346
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine consultation for patients with diabetes mellitus: a cluster randomised controlled trial

Abstract: Introduction There is a widening discrepancy between the increasing number of patients with diabetes mellitus and the health care resources available to manage these patients. Telemedicine has been used in a number of instances to improve and deliver health care where traditional care delivery methods may encounter difficulty. We conducted a cluster randomised controlled trial of telemedicine consultation to manage patients with diabetes mellitus. Methods Eleven primary care centres attached to one Veteran Adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 17 publications
0
66
0
Order By: Relevance
“…Our findings are in line with those of other studies that suggest that diabetes care via telemedicine is comparable to in-person diabetes care. For example, in a recent randomized controlled trial of 282 diabetes patients, those who received telemedicine consultation had a −1.01% decrease in hemoglobin A1c compared with a −0.68% decrease in hemoglobin A1c in those receiving in-person consultation, although the change was nonsignificant ( 14 ). Our findings, which demonstrated a 0.6% decrease in hemoglobin A1c at 12 months of telemedicine follow-up consultation, complement this study’s findings and growing evidence that suggests that telemedicine is a viable alternative for in-person care.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in line with those of other studies that suggest that diabetes care via telemedicine is comparable to in-person diabetes care. For example, in a recent randomized controlled trial of 282 diabetes patients, those who received telemedicine consultation had a −1.01% decrease in hemoglobin A1c compared with a −0.68% decrease in hemoglobin A1c in those receiving in-person consultation, although the change was nonsignificant ( 14 ). Our findings, which demonstrated a 0.6% decrease in hemoglobin A1c at 12 months of telemedicine follow-up consultation, complement this study’s findings and growing evidence that suggests that telemedicine is a viable alternative for in-person care.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of literature shows that telemedicine entails positive outcomes including improving treatment of patient symptoms and disease management. [2][3][4][5][6][7] Patients feel that telemedicine yields high satisfaction, allows good communication, saves time, and is cost-effective. [5][6][7][8][9][10] Telemedicine decreases hospitalization rates and visits to the emergency room.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] In the few reported studies, the results of telehealth were variable; some studies showed that telehealth could generate statistically significant improvements in clinical outcomes, diabetes-related expenditures, hospital admissions and hospitalizations, [ 9 11 ] and other studies have claimed that telehealth is similar to usual care for diabetes control. [ 12 , 13 ] Thus, the objective of this systematic review was to compare the clinical outcomes of telehealth and usual care in the management of diabetes. This study focused mainly on trials with a large sample size (n > 100) and a long-term intervention (duration > 6 months) to provide rigorous evidence for policy makers.…”
Section: Introductionmentioning
confidence: 99%